2007
DOI: 10.5005/jcdp-8-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Time Periods of Vital Bleaching on Flexural Strength of Bovine Enamel and Dentin Complex

Abstract: Aim The aim of this in vitro study was to evaluate the effect of 20% carbamide peroxide (CP) on the flexural strength (FS) of bovine enamel and dentin complex. Methods and Materials One hundred sound bovine teeth were selected for use. Blocks (2×3×8 mm) from the middle portion of the facial surfaces of each crown were sectioned from the teeth. The specimens were randomly divided into five groups (n=20) based on the time period of vital bleaching. Group 1 comprised the control group kept in artificial saliva.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…These ultra-structural alterations increase dentin permeability 11 , reduce hardness and elasticity. 12,17,22 Chng et al 17 reported a significant decrease in the ultimate tensile and shear strengths of dentin after intracoronal bleaching with 30% hydrogen peroxide for 24 h. Recently, Ghavamnasiri et al 30 also showed that the flexural strength of bovine dentin decreased after the application of j o u r n a l o f d e n t i s t r y 3 6 ( 2 0 0 8 ) 9 3 5 -9 3 9…”
Section: Discussionmentioning
confidence: 94%
“…These ultra-structural alterations increase dentin permeability 11 , reduce hardness and elasticity. 12,17,22 Chng et al 17 reported a significant decrease in the ultimate tensile and shear strengths of dentin after intracoronal bleaching with 30% hydrogen peroxide for 24 h. Recently, Ghavamnasiri et al 30 also showed that the flexural strength of bovine dentin decreased after the application of j o u r n a l o f d e n t i s t r y 3 6 ( 2 0 0 8 ) 9 3 5 -9 3 9…”
Section: Discussionmentioning
confidence: 94%
“…There are few studies that evaluated the mechanical properties of dentin submitted to tooth bleaching (15,16,20,21). Pobbe et al (16) found that the fracture strength of teeth was reduced after three sessions of internal bleaching with 38% hydrogen peroxide.…”
Section: Effect Of High-concentrated Bleaching Agents On the Bond Strmentioning
confidence: 99%
“…21 The flexural strength of bovine dentin was significantly reduced by an application of 20% carbamide peroxide bleach for 2 weeks. 22 In another in vitro study, the fracture toughness of dentin was significantly reduced by the indirect (through intact enamel) application of peroxide bleaching agents (this represents a simulation of clinical bleaching of teeth with full enamel coverage), as well as by a direct bleach application method to dentin, and that it was reduced more for the longer application time period (8 versus 2 weeks) and for the higher (16% versus 10%) bleach concentration. 23 The clinical relevance of these in vitro studies is uncertain and in vivo studies are lacking.…”
Section: Introductionmentioning
confidence: 98%